Efficacy of Houttuynia cordata Lour extracts against herpes simplex virus infection - Pratya Chaliewchalad" (Science Faculty of Chiang Mai University, 2019)
The efficacy of the aqueous and ethanolic extracts of Houttuynia cordata Lour in inhibiting herpes simplex virus (HSV) is demonstrated in this present study. The inhibitory effect of the plant extracts in the various stages of the HSV multiplication cycle was investigated using plaque reduction assay. The result showed that the CD50 values of the aqueous and ethanolic extracts of H. cordata were 2845.3 μg/ml and 1426.0 μg/ml, respectively. The highest anti-HSV-1 and HSV-2 of the aqueous extract of H. cordata was observed when the extract was treated during viral attachment with therapeutic index (TI) values of 3.51±0.0 and 4.48±0.11. However, the ethanolic extract of H. cordata showed the highest direct inactivation of both the types of HSV at 20 minutes of treatment. Furthermore, it was observed that viral multiplication was inhibited with the highest reduction of log HSV-1 and HSV-2 titers at 30 hours after treatment with the ethanolic extract of H. cordata. The ethanolic extract of H. cordata also exerted potent inhibitory effect against viral DNA and protein synthesis. Therefore, the H. cordata plant extract should be used as a potential medicinal plant for the treatment of herpes simplex virus infection.